THE EFFECT OF FINANCIAL LITERACY AND INCLUSION ON THE PERFORMANCE AND SUSTAINABILITY OF GROCERY STORES IN PROBOLINGGO REGENCY. - Titin Krisnawati; Tatik Amani; Umi Habibah (Politeknik Negeri Ambon, 2025)
Introduction: SMEs are known as a resilient sector against shocks and economic crises, as evidenced during the monetary crisis and the COVID-19 pandemic when SMEs were able to survive and even contributed to maintaining national economic stability. Financial literacy and inclusion play an important role in the sustainability and improving the performance of SMEs. Methods: The research method used is quantitative, with financial literacy and financial inclusion as independent variables and business performance and sustainability as dependent variables. The sample in this study consists of 44 Micro Enterprises registered with DKUPP Probolinggo Regency. Data collection was conducted using interviews, questionnaires, and documentation. The data analysis technique used was SmartPLS 4.0. Results: Research findings indicate that the variable of financial literacy has an impact on the performance and sustainability of Micro Enterprises (Grocery Stores), while the variable of financial inclusion does not affect the performance and sustainability of Micro Enterprises (Grocery Stores) registered in the DKUPP Probolinggo Regency. Financial literacy affects the performance and sustainability of micro-enterprises (grocery stores). This indicates that micro-business actors (grocery stores) already have good financial literacy. Financial inclusion does not affect the performance and sustainability of micro-enterprises. Although access to financial services is available, business actors have not fully utilized financial products and services optimally. DKUPP needs to develop training and mentoring programs to enhance the skills and knowledge of business actors, especially regarding financial inclusion. Keywords: Financial Literacy, Financial Inclusion, Performance, Sustainability.